Perfil clínico e laboratorial de crianças e adolescentes em uma unidade de hemodiálise: um estudo retrospectivo - Freitas, Johnathan Santana de (2013)
Chronic kidney disease (CKD) is defined as the presence of kidney damage and / or loss of renal function over a period longer than three months. In stage 5 CKD signs of uremia, requiring one of the modalities of renal replacement therapy, hemodialysis among them. In children with CKD is important to identify and treat anemia, and frequent complication related to decreased quality of life (with losses in neurocognitive development, attention in school and physical capacity), increased mortality and hospitalization, and increased rates by cardiac lead to left ventricular hypertrophy. This work was carried out to evaluate the adequacy of hemodialysis received by children and adolescents with chronic renal failure (CRF) undergoing hemodialysis at Hospital of the Federal University of Goiás (UFG-HC), analyzing clinical data for this and laboratory of these patients over a period of 2 years. A retrospective study in which patients were selected until 18 years of age with chronic kidney disease on hemodialysis in HC-UFG between 09/01/01 and 31/12/10. We checked the records in search of clinical and laboratory data. Statistical analysis was performed with the Kolmogorov-Smirnov test, Pearson-Chi Square, Fisher’s Exact test and generalized estimating equation (GEE) in Statistical Package for the Social Sciences 20, assuming a significance level of 5%. We analyzed 358 medical records of monthly evolution of 29 patients. The most common etiology for chronic kidney disease was malformation of the genitourinary tract (28.0%). Hemoglobin is a parameter of the normal distribution with a mean value of 9.20 ± 1.84 g / dL, below the recommended values in 65.26% of the chips. THE GEE, infection of double-lumen catheter was a risk factor for anemia (odds ratio 2.7, 95% confidence interval 1.1-6.8, p = 0.034). The use of intravenous iron hydroxide was protective (odds ratio 0.4, 95% confidence interval 0.2-0.9, p = 0.029). The main cause of CRF in the study population were congenital malformations of the genito urinary tract. There was a predominance of arteriovenous fistula for dialysis. The dialysis prescription was in accordance Abstract xvi with the recommendations in the literature. Secondary hyperparathyroidism, hypertension, dyslipidemia and heart diseases were prevalent. The delayed immunization was low and access to kidney transplantation was significant. The Kt/V was appropriate. Control of acidosis was the next recommended. The use of specific drugs to the DRC as erythropoietin and intravenous iron hydroxide calcitriol was in accordance with the Brazilian reality. The markers of iron stores (ferritin and TSAT) were adequate. The serum calcium values were adequate in 38% of patients and serum phosphorus was most appropriate. All these data are in accordance with those found in other services. Drew attention the high rate of anemia, which is aggravated by catheter infection. The use of iron hydroxide was formed on protective factor. The lack of standardization for the values of anemia in children on hemodialysis difficult to compare the data.